Anxiety and attitudes towards sex in women requesting emergency contraception - Ernesto S. González-Mesa; Lorena Bueno-Cobos; Nuria Barroso-García; José C. Vilches-Jiménez (Taylor & Francis Group, 2019)
We performed an observational descriptive study on 89 women who requested for emergency contraception (EC) at the emergency units of two hospitals, Virgen de la Victoria Hospital, and Regional University Hospital in Malaga between October 2016 and April 2017. Both hospitals are on the Andalusian Public Health System. We evaluated a group of socio-demographic variables and others related to the beliefs and the knowledge about EC and contraception in general, sexual behavior, Eysenck's Inventory of Attitudes to Sex (satisfaction and promiscuity factors), and State-Trait Anxiety Inventory (STAI). RESULTS: State anxiety scores were low in 10.8% of the participants, middle in 25.7% and high in the 63.5%. On the other hand, the scores for trait anxiety were low in 13.5%, middle in 39.2% and high in 47.3%. The demand for EC resulted in a stressful situation for women, especially for youngest women. Also, married women with children and a history of pregnancy terminations showed higher anxiety scores. Regarding sexual attitudes, the highest levels of anxiety (state and trait) were found in women with less knowledge about EC, and in those who reported less satisfaction with their sex life. Best fit regression models for anxiety levels included beliefs that ECs are abortive, sexual dissatisfaction and women's age as predictive variables for STAI scores. In conclusion, women who requested EC showed high scores in anxiety-state and -trait, with those of younger age presenting more intense emotions.